Sistem Pakar untuk Mendiagnosa Penyakit Saluran Pernapasan pada Anak (Studi Kasus : RSAB HARAPAN KITA JAKARTA): SISTEM PAKAR UNTUK MENDIAGNOSA PENYAKIT SALURAN PERNAPASAN PADA ANAK (Studi Kasus : RSAB HARAPAN KITA JAKARTA) - Kuryanti, Sandra Jamu; Septiani, Minda (Politeknik Ganesha Medan, 2018)
Expert systems are computer-based system that uses knowledge, facts, and reasoning techniques to solve problems that normally can only be solved by an expert in a particular field. Expert systems provide added value in technology to assist in dealing with increasingly sophisticated information age. Expert System application generates output in the form of the possibility of respiratory diseases suffered by the symptoms felt by the user. The system uses a forward search method (Forward Chaining) to find a solution or possible illness suffered by the user.